2019
DOI: 10.1109/tmi.2019.2905990
|View full text |Cite
|
Sign up to set email alerts
|

TeTrIS: Template Transformer Networks for Image Segmentation With Shape Priors

Abstract: In this paper we introduce and compare different approaches for incorporating shape prior information into neural network based image segmentation. Specifically, we introduce the concept of template transformer networks where a shape template is deformed to match the underlying structure of interest through an end-to-end trained spatial transformer network. This has the advantage of explicitly enforcing shape priors and is free of discretisation artefacts by providing a soft partial volume segmentation. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…In particular, with respect to challenges such as generalisability, explainability and data efficiency it is likely that the combination of traditional model-and data-driven approaches will lead to future advances. Several approaches have already demonstrated that priors in form of anatomical models can significantly improve the performance of applications such as segmentation [67,21] or super-resolution reconstruction [84].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, with respect to challenges such as generalisability, explainability and data efficiency it is likely that the combination of traditional model-and data-driven approaches will lead to future advances. Several approaches have already demonstrated that priors in form of anatomical models can significantly improve the performance of applications such as segmentation [67,21] or super-resolution reconstruction [84].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it is beneficial and important to incorporate shape priors of the segmentation object with the segmentation models for improved performance and accelerated convergence. A strong reason is that shape is one of the most important geometric attributes of anatomical objects [21] , and the shape priors can reduce the searching space of the potential segmentation outputs for deep learning models [22] . In addition, the shape mesh provides sufficient information for the identification of 3D objects [23] .…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al (44) used centerlines to obtain a reformatted image in which the lumen was segmented using a 3D CNN. Lee et al (42) use centerlines to obtain a tube-shaped prior that is deformed to segment the coronary lumen. Lumen segmentation is often considered a preprocessing step for stenosis detection, but it has been shown that stenosis degree can also be directly determined based on image data.…”
Section: Anatomical Significancementioning
confidence: 99%